MENINGKATKAN HASIL BELAJAR GERAKAN DASAR TENIS MEJA MELALUI MODIVIKASI ALAT MEDIA DINDING DI KELAS V SD NEGERI 115/II BEDARO - DEKA ISMI MORI SAPUTRA; M Subhan (LP3M Universitas Muhammadiyah Muara Bungo, 2019)
The background of this research is the classical teaching-learning process that will face heterogeneous problems with students' abilities. Where the lack of creativity of a physical education teacher in packaging physical education learning materials is considered to be the cause, so many students do not complete KKM grades. The research objective to be achieved is to find out the application of the modification of wall media tools to improve learning outcomes of table tennis basic movements in class V of SDN 115 / II Bedaro. The study used a Class Action Research design which was carried out in two cycles, each cycle consisting of planning, implementing actions, observing and reflecting. The subjects of this study were Class V students of Bedaro 115 / II Elementary School, totaling 22 students. Table tennis learning outcome data obtained through performance tests, observation sheets are used to collect data on student activities in following the table tennis learning process with wall media modification methods. The results of this study were obtained based on an assessment of three aspects, namely psychomotor, affective, and cognitive. Table tennis learning through wall media can improve the learning outcomes of students in class V of Bedaro 115 / II Elementary School. This can be seen from the increase in learning outcomes from pre cycle, cycle I to cycle II. In the pre cycle which is 68.2%, cycle I is 71.8%, and cycle II is 83.3%. From the number of complete categories the number of students who completed was increased from 7 to 20 students in the second cycle, meaning that there was an increase in students in the complete category by 20.7% of the total number of students 22 of which 20 were declared complete. For physical education teachers in Elementary Schools can apply table tennis learning to the material using the modification tools of the wall media in Physical Education lessons.